1994
DOI: 10.1177/107110079401500103
|View full text |Cite
|
Sign up to set email alerts
|

Clinical, Quantitative Assessment of First Tarsometatarsal Mobility in the Sagittal Plane and Its Relation to Hallux Valgus Deformity

Abstract: Today, bunion surgery is still controversial. Considering that a bunion deformity in fact may be a result of multiple causes, the rationale of the currently applied techniques of surgical treatment has not been conclusively demonstrated. In view of the known hypermobility syndrome of the first ray that results in insufficient weightbearing beneath the first metatarsal head, the relationship between this syndrome and hallux valgus deformity has been investigated. The results suggest a direct relationship betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
209
1
9

Year Published

1999
1999
2020
2020

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 235 publications
(224 citation statements)
references
References 3 publications
5
209
1
9
Order By: Relevance
“…2 The SEM was computed as the square root of within-subjects mean-square error from a 1-way analysis of variance (ANOVA). 2 Intrarater reliability (ICC 3,10 ) for the ruler measurements of each examiner and for the device (ICC 3,1 ) were calculated. Interrater reliability (ICC 2,10 ) for the ruler measurement was calculated using data from the first measurement session.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…2 The SEM was computed as the square root of within-subjects mean-square error from a 1-way analysis of variance (ANOVA). 2 Intrarater reliability (ICC 3,10 ) for the ruler measurements of each examiner and for the device (ICC 3,1 ) were calculated. Interrater reliability (ICC 2,10 ) for the ruler measurement was calculated using data from the first measurement session.…”
Section: Discussionmentioning
confidence: 99%
“…Both groups of investigators found poor agreement between clinicianassessed ordinal-level hypomobile, normal, or hypermobile estimates of the first ray sagittal plane motion as compared to dorsal mobility measured by a mechanical device. 1,4 Authors of clinical studies 9,10,12,15 have suggested ways to refine Morton's test procedure with intent to improve the measure. Grebing and Coughlin 9 found that motion available at the first ray is influenced by the position of the ankle and recommended that a neutral ankle position with the knee bolstered in slight flexion be adopted as the standard position of measurement.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, hallux valgus deformity decreased in frequency as facet number increased, with the condition identified in all seven feet (100%) with a unifacet and 12 (66.7%) of 18 feet with bifacets. Hallux valgus was not encountered in any of the 16 feet with the trifacet pattern, leading the authors to conclude that it restricts the joint hypermobility that some believe to be a precipitating factor (Carl et al, 1988;Klaue et al, 1994). The rarity of the unifacet pattern, often noted as one of the most frequently occurring patterns at the hallucal tarsometatarsal joint (Singh, 1960;Jeyasingh et al, 1981;Ajmani et al, 1984;Zipfel, 2004) is surprising, as is the high rate of trifacets.…”
Section: Resultsmentioning
confidence: 96%
“…[2][3][4]. In addition, limited Lisfranc complex mobility [2] and medial column sagittal instability [5] are known risk factors for rapid progression of HV. On the other hand, some changes in the hindfoot also appear to be related to HV progression.…”
Section: Introductionmentioning
confidence: 99%